Therapeutic and protective effects of light-cured varnishes on erosive lesions: an in vitro study - Ebru Imren; Yeliz Güven (BMC Oral Health)
Abstract Background This study aimed to investigate the efficacy of light-cured fluoride varnishes on artificial erosive lesions. Methods Thirty extracted third molars were subjected to a 5-day erosive cycle, involving exposure to citric acid (pH 3.6, 4 × 1 min) and artificial saliva (pH 7, 4 × 2 h). The samples were then divided into five groups: light-cured glass ionomer varnish (CXT; Clinpro XT, 3 M™ ESPE, USA), light-cured giomer varnish (PRG; PRG Barrier Coat, SHOFU™, USA), casein phosphopeptide-amorphous calcium fluoride phosphate (MIV; MI Varnish, GC Corp., Tokyo, Japan), 5% sodium fluoride (VPF; Voco Profluorid Varnish, VOCO GmbH, Germany), and distilled water (DW, negative control) groups. After initial erosion, the samples were treated with varnishes and subjected to a second 7-day erosive cycle. The Vickers microhardness and surface roughness were measured at each stage. The therapeutic (rehardening) effects were expressed as the surface microhardness recovery percentage (SMHR%) and roughness progression (RP1%), whereas the protective effects were indicated by relative erosion resistance percentage (RER%) and roughness progression (RP2%). Results The VPF group showed significantly higher SMHR% compared to the control group (p  < 0.05). After the second demineralization, the CXT and PRG groups demonstrated significantly higher RER% than the negative control group (p  < 0.05). Surface roughness measurements revealed no significant differences among the groups (p  > 0.05). Qualitative analysis of profilometric images showed that surface irregularities present after the initial demineralization (t1) were reduced following varnish application at t2. However, after the second erosive cycle at t3, new irregularities were observed, particularly in the DW and VPF groups. Conclusion This study revealed that conventional fluoride varnish exhibited greater therapeutic effects, as evidenced by improved surface microhardness recovery, whereas light-cured varnishes were more effective at providing protection against erosion. These findings highlight the potential of light-cured fluoride varnishes in providing extended surface protection.